Workers of the World? A British Liberal-Pluralist Critique of Marcel van der Linden's Global Labour History*. (2nd August 2017) - Ackers, Peter
Abstract: Marcel van der Linden has championed Global Labour History (GLH) as a solution to the decline of Labour History as an academic field. His 2008 Workers of the World (and other writing) strives to transcend methodological nationalism and provides a new global framework to study labour through the ages. This British liberal-pluralist critique argues that Van der Linden's version of GLH is essentially a re-packaging of Marxism that narrows the conceptual foundations of the field and overlooks both the full political crisis of state-socialism and its limited historical appeal to working people. The article concludes by defending a national approach centred on civil society institutions, as represented in the 2016 collection edited by P. Ackers and A.J. Reid, Alternatives to State-Socialism in Britain: Other Worlds of Labour in the Twentieth Century. Abstract : TRANSLATED ABSTRACTS FRENCH – GERMAN – SPANISH Peter Ackers. Travailleurs du monde? Une critique libérale et pluraliste au Royaume-Uni de l'histoire globale du travail de Marcel van den Linden . Marcel van der Linden a défendu l'histoire globale du travail ( Global Labour History ou GLH) comme solution au déclin de l'histoire globale du travail en tant que champ d'études universitaires. Son Workers of the World de 2008 (et d'autres écrits) tentent de transcender le nationalisme méthodologique et fournit un nouveau cadre global pour étudier le travail à travers les âges. La présente critique libérale et pluraliste au Royaume-Uni soutient que la version de Van der Linden de la GLH est essentiellement une remise en forme du marxisme, restreignant les fondements conceptuels du champ d'études, et négligeant à la fois l'ensemble de la crise politique du socialisme étatique et son attrait historique limité pour les travailleurs. L'article conclut en défendant une approche nationale centrée sur les institutions de la société civile, représentée dans la collection de 2016 révisée par P. Ackers et A.J. Reid, Alternatives to State-Socialism in Britain: Other Worlds of Labour in the Twentieth Century. Traduction: Christine Plard Abstract : Peter Ackers. Arbeiter der Welt? Eine britische, liberal-pluralistische Kritik der globalen Arbeitsgeschichte Marcel van der Lindens . Marcel van der Linden hat die globale Arbeitsgeschichte als Gegenmittel zum Niedergang des akademischen Forschungsfelds Arbeitsgeschichte propagiert. In seinem 2008 erschienenen Buch Workers of the World ist er (wie auch in anderen Schriften) bestrebt, über den methodologischen Nationalismus hinauszugehen und einen neuen, globalen Rahmen für die Erforschung der Arbeit über verschiedene Zeitalter hinweg zu bieten. In dieser britischen, liberal-pluralistischen Kritik wird die These vertreten, dass es sich bei der globalen Arbeitsgeschichte Van der Lindens im Wesentlichen um einen Marxismus im neuen Gewand handelt, der die begrifflichen Grundlagen des Feldes verengt und sowohl die ausgewachsene politische Krise des Staatssozialismus als auch dessen begrenzte historische Attraktivität für arbeitende Menschen ignoriert. Der Beitrag schließt mit der Verteidigung eines auf die Nation zentrierten Ansatzes, der zivilgesellschaftliche Institutionen in den Mittelpunkt stellt, wie dies in dem 2016 erschienenen, von P. Ackers und A.J. Reid herausgegebenen Sammelband Alternatives to State-Socialism in Britain: Other Worlds of Labour in the Twentieth Century geleistet worden ist. Übersetzung: Max Henninger Abstract : Peter Ackers. ¿Trabajadores del mundo? Una crítica liberal-pluralista británica a la Historia Global del Trabajo de Marcel van der Linden . Marcel van der Linden ha propuesto la Historia Global del Trabajo (HGT) como una solución al declive de la Historia del trabajo en tanto disciplina académica. Su obra de 2008 Workers of the World (entre otros de sus muchos trabajos) es un esfuerzo por trascender el nacionalismo metodológico y por proveer un nuevo maco global para el estudio del trabajo en el transcurso del tiempo. La crítica liberal-pluralista británica considera que la versión de Van der Linden respecto a la HGT es, esencialmente, un la reelaboración de un marxismo que estrecha los fundamentos conceptuales del campo de estudio y pasa por alto tanto la crisis política total del socialismo de Estado como los limitados atractivos históricos para la clase trabajadora. El artículo concluye con una defensa de una aproximación nacional centrada en las instituciones de la sociedad civil, como la que se propone en la obra colectiva de 2016 coordinada por P. Ackers y A.J. Reid, Alternatives to State-Socialism in Britain: Other Worlds of Labour in the Twentieth Century. Traducción: Vicent Sanz Rozalén